Sistem Pakar Diagnosa Tingkat Depresi Pada Lansia Di Balai Sosial Tresna Werdha Menggunakan Metode Certainty Factor - AzhariMalindo, M.; Chandra, Albert Yakobus (CV. Information Technology Training Center - Indonesia (ITTC), 2021)
Depressive disorder in the elderly is a clinical and public health issue that has yet to be addressed. The elderly who live at home with their families have better physical, psychological, and environmental health than those who live in orphanages. Mental health issues, particularly depression, frequently go undiagnosed in the elderly. This is because older people who are depressed often have physical symptoms like insomnia, loss of appetite, stomach problems, and headaches. When older people are depressed, their bodies tend to hurt more. It is hard to tell whether someone is complaining about their body or mind, so depression is often found too late. To anticipate these issues, an expert system was created that can take the place of an expert in solving the problem. A clinical psychologist is an expert in the field of elderly depression. This study classified elderly depression into three levels: mild depression, moderate depression, and major depression. This study was carried out with the help of a case study from the Tresna Werdha Pakem Social Center in Sleman, DI Yogyakarta.The Certainty Factor method was used to make an expert system for determining how depressed an older person is. This is because it is a sure thing based on evidence or an expert's opinion. The goal of developing an expert system for diagnosing depression in the elderly is for expert and non-expert officers to diagnose the level of depression in the elderly. Based on 10 elderly data that the system and experts have tested by applying the Certainty Factor method, the accuracy was 98%.